Experimental and numerical study of the damage mechanisms in hybrid unidirectional/woven composites under impact loading. (1st February 2019) - Mahmoud, B.; Manseri, L.; Rogani, A.; Navarro, P.; Marguet, S.; Ferrero, J-F.; Tawk, I.
Abstract: This paper deals with low velocity and medium velocity impacts on thin carbon/epoxy hybrid laminates made of unidirectional plies and woven fabric layers. Drop weight and gas gun impact tests were performed to compare the damage mechanisms of thin hybrid laminates with those of woven laminates of equivalent stiffness and mass. The results show that hybrid laminates present a better impact behaviour in terms of post impact damage extent. These tests were then modeled using a semi-continuous approach. The numerical results well correlate the experiments.